GAMBARAN KESEHATAN WARGA DUSUN BERAN, DESA DIBAL, KECAMATAN NGEMPLAK, KABUPATEN BOYOLALI, JAWA TENGAH - Wibowo, Yudi; Listiana, Endah; Anggraini, Fadila (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Awareness of rural communities in Indonesia to carry out health checks in general is still low, this is widely evidenced by the results of research that has been published in various health journals. The purpose of this service activity is an effort to check health and socialize disease prevention in Desa Dibal, Kecamatan Ngemplak, Kecamatan Boyolali, Central Java province. The health checks are in the form of checking blood pressure, blood sugar, and uric acid. In addition to health checks, residents also receive direct counseling regarding a healthy daily diet to prevent diseases such as hypertension, diabetes, and gout. This health check-up and counseling activity is carried out by visiting events that are being held by residents of Dibal Village RT 04 RW 05, namely during PKK activities for mothers and during posyandu activities in RW 05. Participants in free health check-ups are dominated by women, as many as 50 people with an age range of 25-60 years. The results of blood pressure measurements of participants for free health checks found many people with hypertension.